The flood risk in the current context of climate change. Didactic proposals to teach in the school Geography: El riesgo de inundación en el contexto actual de cambio climático. Propuestas didácticas para su enseñanza en la Geografía escolar (2021)
In Spain, the importance of teaching atmospheric risks has reached the political sphere with the intention of improving how these contents are treated in non-university stages. This interest is determined by the fact that education is an action of vital necessity to increase the adaptation and resilience of natural risks in the current context of climate change, as reflected in the 2030 Agenda (United Nations Organization). The objective of this work is to propose didactic activities (Spanish context) in the subject of Geography (Secondary Education and Baccalaureate) on the risk of flooding, one of the main effects associated with the climate warming process in the Mediterranean region. With its implementation it is intended, on the one hand, to eliminate the deficiencies evidenced in the training of students in relation to the sources from which they obtain information, and on the other, to promote the importance that education has in the prevention and mitigation of risks climatic. This proposal has also been prepared with the intention of being a guide to be implemented in other regions with similar climatic and socio-economic characteristics.